Question
What is \( (f-g)(x) \) ? \[ f(x)=x \] \( g(x)=3 x^{2}+9 x \) Write your answer as a polynomial or a rational function in simplest form. Save answer
Ask by Little Boyd. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( (f - g)(x) = -3x^{2} - 8x \)
Solution
To find \( (f - g)(x) \), subtract the function \( g(x) \) from \( f(x) \):
\[
(f - g)(x) = f(x) - g(x)
\]
Given:
\[
f(x) = x
\]
\[
g(x) = 3x^2 + 9x
\]
Substitute these into the equation:
\[
(f - g)(x) = x - (3x^2 + 9x)
\]
Distribute the negative sign:
\[
(f - g)(x) = x - 3x^2 - 9x
\]
Combine like terms:
\[
(f - g)(x) = -3x^2 + (1x - 9x)
\]
\[
(f - g)(x) = -3x^2 - 8x
\]
**Final Answer:**
\[
(f - g)(x) = -3x^{2} - 8x
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Bonus Knowledge
To find \( (f-g)(x) \), we need to subtract \( g(x) \) from \( f(x) \): \[ (f-g)(x) = f(x) - g(x) = x - (3x^2 + 9x) \] Now, simplifying: \[ (f-g)(x) = x - 3x^2 - 9x = -3x^2 - 8x \] Thus, the answer is: \[ (f-g)(x) = -3x^2 - 8x \]